On zero-free regions for the derivative of a polynomial (BIBECHANA, 2016)
Let Pn denote the set of all polynomials of the form p(z) =z∏n-1j=1(z-zj)  with |zj|≥1, 1≤ j≤ n-1. In this paper we shall obtain some zero-free regions for the derivative of a polynomial.BIBECHANA 14 (2017) 48-53